1984
DOI: 10.1097/00004032-198404000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Early Lung Clearance of Yellowcake Aerosols in Rats With in Vitro Dissolution and IR Analysis

Abstract: The lung retention of uranium was determined in rats that inhaled aerosols of commercial yellowcake powders obtained from two mills (Mill A and Mill D) and whose chemical composition and solubilities in vitro were significantly different. Analysis by IR absorption indicated Mill A yellowcake contained 82% ammonium diuranate (ADU) and 18% U3O8. The Mill D powder contained 25% ADU and 75% U3O8. In vitro dissolution studies indicated for the Mill A sample, approximately 85% of the uranium had a dissolution half-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 2 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…It is a typical synthetic lung fluid that mimics the surfactant fluids released by type II alveolar cells. This liquid solution was first used for determining the in vitro toxicity of radioactive compounds in lungs and has been validated (Damon et al 1984). Moreover, its composition (Table 1) is very comparable to the real fluid in human alveolar lung in terms of major components, especially with the addition of DPPC (dipalmitoylphosphatidylcholine), which is the main phospholipid (65 %) found in the alveolar fluid.…”
Section: Composition Of the Simulated Alveolar Lung Fluidmentioning
confidence: 98%
“…It is a typical synthetic lung fluid that mimics the surfactant fluids released by type II alveolar cells. This liquid solution was first used for determining the in vitro toxicity of radioactive compounds in lungs and has been validated (Damon et al 1984). Moreover, its composition (Table 1) is very comparable to the real fluid in human alveolar lung in terms of major components, especially with the addition of DPPC (dipalmitoylphosphatidylcholine), which is the main phospholipid (65 %) found in the alveolar fluid.…”
Section: Composition Of the Simulated Alveolar Lung Fluidmentioning
confidence: 98%
“…Subsequently, various studies have employed the method for determining the bioaccessibility of radioactive compounds (Damon et al 1984). Davies and Feddah (2003) showed that simulated lung fluid considered in their study is identical to fluid sampled from human lungs in terms of major components.…”
Section: Simulated Lung Fluidmentioning
confidence: 99%
“…Twenty beagle dogs from the Institute's colony ( 10 male and 10 female, 2 to 6 y of age) were exposed by pernasal inhalation (Boecker et al 1964). Aerosols were generated from dry powders, using a DeVilbiss Model 175 * powder blower affixed to a mechanical shaker (Damon et al 1984). The aerosols were sampled using cascade impactors to measure particle size distribution (Mercer et al 1970) and 0.45-pm pore size membrane filters to measure airborne U concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Individual measurements, or even a series of measurements, might be uncertain by a factor of 10. However, if the inhaled material is unknown and a simulation model is not applied, the results would be uncertain by a factor of 1000 (Eidson 1984).…”
Section: Scaling To Manmentioning
confidence: 99%